The Influence of Brand Image, Product Quality, and Service Quality on Kredit Guna Bakti (KGB) Loan Decisions for TNI AD Customers at Bank BJB Cimahi Branch - Siska Lesanuari; Paramita, Veronika Santi (Yayasan Sinergi Kawula Muda, 2025)
The increasing competition in the globalised business era requires all banks to innovate and provide the best services to their customers continuously. This is also felt by Bank BJB Cimahi Branch, which faces the challenge of a decline in interest from Indonesian Army (TNI AD) customers toward the Kredit Guna Bakti (KGB) loan product, despite offering various advantages such as competitive interest rates and quality services. This study aims to analyze the influence of brand image, product quality, and service quality on the credit decisions of Indonesian Army (TNI AD) customers using the Kredit Guna Bakti (KGB) facility at Bank BJB Cimahi Branch. Using a quantitative approach and random sampling method, data from 78 respondents were analyzed through multiple linear regression tests. The results show that brand image, product quality, and service quality positively and significantly impact credit decisions both individually and simultaneously. These findings emphasize the importance of strengthening brand image, product innovation, and improving service quality in influencing customer decisions. This study provides practical contributions to Bank BJB in designing more effective marketing and service strategies to increase customer interest in the KGB facility.